Poetics and the teaching of poetry to English first language higher grade pupils in the senior high school - Dixon, C. K. J.(Clive Kenneth John) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1985.